2005
DOI: 10.4049/jimmunol.174.9.5562
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking of CD23: Differential Regulation in Humans and Mice by Both Extracellular and Intracellular Exons

Abstract: In mouse models of food allergy, we recently characterized a new CD23b-derived splice form lacking extracellular exon 5, bΔ5, which undergoes constitutive internalization and mediates the transepithelial transport of free IgE, whereas classical CD23b is more efficient in transporting IgE/allergen complexes. These data suggested that regulation of endocytosis plays a central role in CD23 functions and drove us to systematically compare the intracellular trafficking properties of human and murine CD23 splice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
(82 reference statements)
1
26
0
Order By: Relevance
“…This data are summarized in Table 1. CD23 co-localization with EEA1 and Rab11 indicates endosomal trafficking and is in agreement with previous work that showed that CD23 traffics through the endosomal pathway (31,32).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This data are summarized in Table 1. CD23 co-localization with EEA1 and Rab11 indicates endosomal trafficking and is in agreement with previous work that showed that CD23 traffics through the endosomal pathway (31,32).…”
Section: Resultssupporting
confidence: 93%
“…To further investigate this phenomena, we first sought to confirm studies (31,32) that showed that anti-CD23 cause ligand internalization. mCD23 ϩ -CHO cells were labeled with FITC-anti-CD23 (FITC-B3B4), which is an antilectin mAb, transferred to 37°C and internalization was followed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because offspring of naive mothers were devoid of OVA-specific IgE and the fact that no mechanism to facilitate transplacental transport of IgE is thought to exist in mice or humans, the presence of OVA-specific IgE in serum of nursing offspring suggested that acquisition of maternal IgE from immune mothers was a result of intestinal absorption from breast milk. The low-affinity IgE receptor, CD23, is expressed by intestinal epithelial cells and specific isoforms are responsible for absorption of IgE or IgE immune complexes from the intestinal lumen (74,75). The potential for repercussions from maternally transmitted IgE or IgE immune complexes from breast milk are likely significant in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…CD23 and a novel CD23b-derived alternative splice form CD23b⌬5 in rapid transepithelial transport of IgE/allergen complexes and subsequent delivery of intact antigen to mast cells in the subepithelial compartment (77,78).…”
Section: Fc⑀rii/cd23mentioning
confidence: 99%